Analisis Nilai Tambah dan Usaha Pengolahan Tepung Sukun Sebagai Upaya Peningkatan Pendapatan Petani - Waryat, Waryat; Yanis, Muflihani; Mayasari, Kartika (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2016)
Bread fruit processing into flour is an alternative way of processing which is has several advantages including; increase the shelf life, facilitate the process of raw materials and increase the selling price, while its nutrient is relatively unchanged. The purpose of this study is to examine the amount of value added product generated by bread fruit flour and to determine business analysis of bread fruit flour in Kepulauan Seribu, DKI Jakarta Province. Data is collected using interviews, observation and mutilation. Measurement is done by calculating the value added products resulting from the processing of bread fruit into bread fruit flour, while analysis of feasibility is calculated based on the analysis of profit and analysis of revenue and costs as well as the R/C ratio. Breadfruit flour business has gave product value added, profit and R/C ratio account Rp. 5,500 per kilogram, Rp. 218,000 and 1.57 respectively.